2015
DOI: 10.1002/pen.24163
|View full text |Cite
|
Sign up to set email alerts
|

On‐line multivariate optimization of injection molding

Abstract: An auxiliary process controller was designed, implemented, and validated for on-line process and quality optimization. The objective function included terms related to the process variation, model uncertainty, and control energy. The controller architecture relied on characterized models including both process transfer functions and principal components analysis to perform online optimization in parallel with the physical molding process. New process and quality observations were input to the controller to upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…e model-free optimization (MFO) algorithm is also an effective method. Johnston et al [160] and Yang et al [161] developed an online, model-free process optimization method and obtained ideal convergent results. A systematic approach that combined digital image processing (DIP) and model-free optimization (MFO) was proposed to solve optimization problems [161].…”
Section: Iterative Optimization Methodsmentioning
confidence: 99%
“…e model-free optimization (MFO) algorithm is also an effective method. Johnston et al [160] and Yang et al [161] developed an online, model-free process optimization method and obtained ideal convergent results. A systematic approach that combined digital image processing (DIP) and model-free optimization (MFO) was proposed to solve optimization problems [161].…”
Section: Iterative Optimization Methodsmentioning
confidence: 99%
“…Analyses to identify the most significant process variables that influence key quality attributes, such as dimensional and mechanical properties, in IM can be found in Refs. . For instance, Yang and Gao found that packing pressure, melt temperature, and mold temperature are the most significant process variables that affect part weight on an IM plate.…”
Section: Applicationsmentioning
confidence: 99%
“…Automatic control systems are widely proposed in industrial application to automatically regulate and reject disturbances in processes. [ 9–14 ] EBM can benefit from control systems to automate die gap programming and reduce machine drift. Feedback systems could change the die gap (input) automatically to obtain a desired extrudate thickness (output) or to compensate for any machine drift.…”
Section: Introductionmentioning
confidence: 99%